Sustainable Development in Creative Industries: Embracing Digital Culture for Humanities PROCEEDINGS OF THE 9TH BANDUNG CREATIVE MOVEMENT INTERNATIONAL CONFERENCE ON CREATIVE INDUSTRIES (BCM 2022), BANDUNG, INDONESIA, 1 SEPTEMBER 2022 - Sintowoko, Dyah Ayu Wiwid; Resmadi, Idhar; Azhar, Hanif; Gumilar, Ganjar; Wahab, Taufiq (Taylor & Francis, 2023)
This book provides the thoughtful writings of a selection of authors illustrating a central concept: Sustainable Development in Creative Industries, which utilizes a monetary equilibrium addressing issues, particularly those associated with the use of an integrated area in cyberspace and physical space, and their effect on the creative industries. 15 universities from Asia and Europe have participated in the 9th Bandung Creative Movement, where this topic was explored. Sustainability issues are now at the forefront of progress. The book covers four main areas. The first section, entitled "Art, Culture, and Society," delves into the various sectors that contribute to building a more sustainable environment, including the arts and culture. Whereas, "Design and Architecture" is referring to cutting-edge practices in the fields of manufacturing, transportation, interior design, and building construction. The third section "Technology and New Media" delves into the transformation of technology into a new medium for the development of the creative industries. The final section, "management and Business," discusses an innovative perspective on the state of the market and management in the sector. Anyone interested in the intersection of creative industries, sustainability, and digital cultures would benefit intellectually from reading this book. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license. Funded by Telkom University, Indonesia.